La cripta del paleontologo. Anasemie transfenomenologiche - Facioni, Silvano (Bollettino Filosofico, 2021)
In Jacques Derrida’s long confrontation with psychoanalysis, besides the names of Freud and Lacan, a special place must be reserved for Nicolas Abraham and Maria Torok. With these two psychoanalyst friends, scholars of Sandor Ferenczi and representatives of the Hungarian psychoanalytic school, Derrida had a long exchange and produced some important texts that can revive the debate between deconstruction and psychoanalysis today. This contribution aims to take a first look at this comparison, identifying the theoretical coordinates of a path that is still little explored in the studies dedicated to Derrida. Keywords: Anasemia, Crypt, Death, Symbol, Transphenomenology